Female and Male Myths about Sexuality: A Systematic Review - Faezeh Habibnejad Roushan; Marzieh Azizi; Farangis Habibi; Soghra Khani (علوم بهداشتی ایران, 2025)
Background and Purpose: Individuals’ beliefs about sexuality are, at times, founded on exaggerated, invalid, and unscientific concepts. Such false notions influence current sexual attitudes and behaviors in female and male populations. From this perspective, the present study reviewed the most common myths around sexuality among women and men. Materials and Methods: This systematic review was conducted on various databases, including PubMed, Google Scholar, Magiran, Scopus, PsycINFO, IranDoc, Ovid, ProQuest, Scientific Information Database (SID) and the Cochrane Library. For this purpose, the relevant studies published from 1990 to 2022 were retrieved. After screening the given studies with reference to their abstracts, 7 cross-sectional and comparative studies were included in this systematic review. Results: Based on the search, 281 articles were obtained. The quality of the studies was assessed using the newcastle-ottawa scale (NOS). So, based on these studies, the female and male myths about sexuality could be divided into 5 main domains: Sexual functioning, practice and behavior, body image and sexual identity, first sexual intercourse and sexuality in special situations. Conclusion: The review of the selected articles revealed that female and male populations had multiple myths behind their beliefs about sexuality, depending on numerous factors. Moreover, it was suggested to provide sex education to the general population by healthcare providers (HCPs), particularly through incorporating it into school curricula.